Digitalization of Arabic Language Learning in Minority Areas: The Effectiveness of Wordwall Media on Students' Reading Skills at Yanyawit School, Southern Thailand - Ahmad Dzaky Mubarok; Toto Suharto; Mahammadaree Waeno (Jurnal Visionary : Penelitian Dan Pengembangan Di Bidang Administrasi Pendidikan, 2026)
Reading skills (Mahārah Qira’ah) are crucial competencies in mastering Arabic as the key to religious literacy, but they pose a complex challenge for Muslim minority students in Southern Thailand. The challenges that arise are influenced by limitations in the language environment (bi’ah lughawiyyah) and the dominance of conventional methods. This study aims to examine the effectiveness of Wordwall interactive learning media in improving the reading skills of students at Yanyawit School, Yala, Thailand, which implements the Blockkhos Curriculum. This study uses a quantitative approach with a quasi-experimental pretest-posttest control group design. The research sample consisted of 30 Matheum Play 4 level students selected through purposive sampling. Data collection instruments included reading ability tests (pre-test and post-test) and student response questionnaires, which were analyzed using a t-test (paired sample t-test). The results of this study indicate that the integration of digital gamification through Wordwall not only improves cognitive scores but also provides comprehensible input that lowers students' affective filters, thereby effectively accelerating Arabic literacy in minority education environments. Digitalitation of Arabic, Thailand Muslim Minorities, Reading Skills.